Corporate Social Responsibility in Small and Medium Sized Enterprises Hotel in Seminyak Area - Dewi, A.A. Ayu Indah Kusuma; Sudiksa, I Nyoman; Kalpikawati, Ida Ayu; Pinaria, Ni Wayan Chintia (Institut Pariwisata dan Bisnis Internasional, 2022)
This research is motivated by the importance of CSR disclosure among SMEs hotel in the Seminyak area that has been implementing CSR. The purpose of this study is to explore the implementation of CSR activities, the media uses to disclose the CSR activities, and the perceived barriers to disclosing CSR activities on the website. This research is a qualitative research. The population would be chosen through observation by direct phone call to each SMEs hotel area with CSR activities and 5 SMEs hotel have been chosen. The data needed was gathered by doing interviews to the owner or manager of each SMEs hotel. The data were analyzed through three activities, such as data reduction, data display, conclusions, and method triangulation. The results revealed SMEs hotel predominantly undertake corporate social marketing, community volunteering, and corporate philanthropy, then used meetings, word of mouth, briefing, WhatsApp, Instagram, and email to disclose their CSR activities. SMEs hotel perceived barriers in disclosing their CSR on the website are CSR disclosure is not needed, CSR disclosure is not their priority, and lack of human resources.